PENGARUH KONTEN PROMOSI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA APOTEK INDAH DI KABUPATEN SIDENRENG RAPPANG - Evi Yunita; Adam Latif; Pratiwi Ramlan; Andi Riska Andreani Syafaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Instagram has become one of the most widely used social media platforms in digital marketing due to its ability to reach a large audience quickly, interactively, and extensively. Through various types of content such as photos, videos, and product information, this platform can influence consumers’ perceptions and behavior, particularly in making purchasing decisions. This study aims to examine the effect of Instagram promotional content on consumer purchasing decisions at Apotek Indah in Sidenreng Rappang Regency.The research employs a quantitative approach, with data collection techniques including observation, documentation study, and the distribution of questionnaires to followers of the official Instagram account of Apotek Indah. The population in this study consists of all 144 followers of the Apotek Indah Instagram account, with a sample of 105 respondents determined using the Slovin formula. The survey data were analyzed using simple linear regression with the assistance of SPSS software to determine the influence of promotional content on consumer purchasing decisions.The results indicate that Instagram promotional content has a positive and significant effect on consumer purchasing decisions, with a significance value of 0.001 < 0.05 and a t-value of 29.961.